Kebijakan Negara dalam Keterlambatan ‎Pengurusan Akta Kelahiran Anak‎ - nafi' mubarok (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2016)
Abstract: Certificate of birth as the legal identity of a child and the state legal recognition to the existence of a child, relating to citizenship and their rights as citizens. Unfortunately, the still high number of Indonesian children who do not have a birth certificate that is caused by (1) the problem of cost, (2) families are less aware of the importance of birth certificates, and (3) lack of completeness of the data/documents. In fact, birth registration is part of a civil registry system that provides protection for the human rights of the status of social and individual benefits for children. At the end of this paper concluded that: (1) a birth certificate is a basic right for children, so that every child should memiliknya; (2) The Government of Indonesia is a major carrier of liability for the protection of children's rights, making it responsible for the